Variations in Elastic and Electrical Properties of Crustal Rocks With Varying Degree of Microfracturation. Issue 7 (10th July 2019) - Pimienta, L.; Orellana, L. F.; Violay, M.
Abstract: This work aims at investigating the effect of varying degrees of microfracturing on the joint elastic and electrical transport properties of rocks. Different crustal rocks were subjected to thermal treatment, expected to induce microfracturing, up to different target temperatures from 100 up to 900 °C. The rocks bulk and pore volumes, P and S wave velocities, and frequency‐dependent electrical impedance were measured before and after the treatment. As the temperature of treatment increased, P and S wave velocities and the electrical formation factor drop and pore and bulk volumes increase. As indicated by the microscopic images, this is consistent with the creation of microcracks. These created microcracks do not affect the properties in the exact same manner, and a strong effect of the initial porosity is observed for electrical formation factor. Extrapolating to low‐frequency field‐scale measurements in water‐saturated reservoir rocks highlights an interesting observation: Both seismic and electrical properties at the field scale might highlight similar variations with increasing damage in all rocks. The maximum amount of decrease expected for all rocks is about 1 order of magnitude in electrical formation factor and 40% decrease in P and S wave velocities. Finally, temperature proved to affect very differently the rocks of varying porosity and mineral content, in ways not fully covered by existing works. Porosity, by increasing the matrix compressibility, damps the degree of microfracturing and crack opening. The distinct behavior in calcite‐pure marble evidences a dominance of anisotropic of thermal expansion over isotropic expansion mismatch. Key Points: Thermal treatments to investigate effects of varying microfracturing in rocks under ambient pressure conditions Large variations in elastic and electrical properties, dependent on rock initial porosity, mostly dominated by crack density over aperture Large difference between quartz‐ and calcite‐rich rocks, indicating little effect of isotropic thermal expansion mismatch